TYPOLOGIES OF DATUK GONG: SINICIZED FORM OF KERAMAT BELIEF IN MALAYSIAN CHINESE RELIGION - Tan , Ai Boay (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2025)
This paper examines the typologies of Datuk Gong worship in Malaysia, with a particular focus on its Sinicized transformation. Based on archival materials and fieldwork carried out between 2018 and 2025 in Malaysia, southern Thailand, Singapore, and Medan Indonesia. The paper identifies two broad categories of Datuk Gong. The first is the keramat-derived form, rooted in Malay animistic traditions and later taken up by local Chinese communities. The second category involves personified figures—especially first-generation Chinese immigrant leaders who died under unusual circumstances and were remembered as martyrs before eventually being deified as Datuk Gong. Although the research covers multiple regions, it remains qualitative. The number of Datuk Gong shrines is very large and unevenly recorded, so this paper selects several representative cases to construct a workable analytical framework. The findings show that keramat-type Datuk Gong may appear through stones, mounds, termitaria, snakes, foxes, or even cannons. Besides that, Chinese communities reinterpreted keramat beliefs and also turned certain local historical figures into protective deities, allowing collective memory to become part of religious practice. By laying out these two major forms more clearly, the paper offers a typological outline that has been missing in previous studies and helps situate Datuk Gong worship within broader discussions of cultural adaptation, local memory, and Chinese religious life in Southeast Asia.